Analysis of personalism in political discourse on social media: Macron’s profile on Instagram - Madrid Cánovas, Sonia (Círculo de Lingüística Aplicada a la Comunicación, 2023)
In this article we analyze the hyper-leadership of the President of the French Republic, Emmanuel Macron, on Instagram. Our aim is to demonstrate the presence of discursive shifts in political discourse because of personalization, the sensationalist approach of the media and the de-ideologization of audiences. From a corpus of 196 publications and applying the semiotic methodology (Semprini, 1995), socio-semiotics (Kress y Van Leuwen, 2006) and textual analysis of discourse (Gallardo, 2018) we show that the politician uses himself to build a brand image or self-branding to offer to his voters-spectators.
Keywords: hyper-leadership; Macron; Discourse; Analysis; Instagram.